Study of the Local Scour Around L-Shape Groynes in Clear Water Conditions - I. Khassaf, Saleh; A. Abbas, Hiba (International Journal of Engineering and Technology, 2018)
River training structures; such as groynes; are efficient engineered methods utilized to protect eroding river banks. But during groynes design stage; the designers faces one of the most significant issues which is the evaluation of the maximum depth of local scour around groynes. This is due to the flow area constriction in the groyne location itself; which in turn cause increasing in local velocity that consequently causes the scour. In the present study, the maximum scour depth around L-shape groyne was computed based on laboratory experiments where different number of groynes and distances between them were used as sort of countermeasures to reduce the scour around the groynes foundations. The results showed clear decreasing in scour depth at increasing number of groynes and also distance between them in the limitation of this study.Â A new formula based on experimental data was derived to calculate the local scour depth. This formula gave R2 =0.903 which reflecting good agreement to the results.Â Â